Analysis of Madrasah Readiness in Implementing a Love-Based Curriculum: A Case Study of MA Darun Najah Margoyoso Pati - Nurul Laili Fauziyah; Anista Ika Surachman (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the readiness of madrasah institutions in implementing a love-based curriculum within Islamic educational settings, particularly at MA Darun Najah Margoyoso Pati. A love-based curriculum is an educational approach that emphasizes values such as compassion, empathy, social responsibility, tolerance, and the development of spiritual character in the learning process. In the context of Islamic education, this approach is highly relevant because it aligns with the principles of Islam as a religion of mercy for all creation (rahmatan lil ‘alamin). Therefore, the integration of love-based values into the educational curriculum is expected to strengthen moral development and character formation among students. This research employs a library research method with a qualitative descriptive approach. The data were collected from various academic sources, including books, scientific journals, educational policy documents, and previous studies related to love-based curriculum implementation and character education in Islamic schools. The data analysis process was conducted through several stages, including data collection, data reduction, data presentation, and conclusion drawing. Through this method, the researcher seeks to develop a comprehensive understanding of theoretical concepts and practical implications of implementing a love-based curriculum within Islamic educational institutions. The findings indicate that the readiness of madrasah institutions in implementing a love-based curriculum is influenced by several important factors, including teacher readiness, institutional policy support, integration of character values into learning activities, and the existence of a supportive school culture that promotes compassion and tolerance. MA Darun Najah Margoyoso Pati demonstrates considerable potential for implementing such a curriculum due to its strong Islamic educational traditions that emphasize moral values, spirituality, and harmonious relationships between teachers and students. However, the successful implementation of a love-based curriculum still requires further improvement, particularly in teacher training, development of innovative learning methods, and systematic integration of love-based values into the curriculum framework. Therefore, strategic collaboration among educators, institutions, and policymakers is necessary to ensure the effective implementation of a love-based curriculum within madrasah education